DESCRIBING AND DRAWING PICTURE TECHNIQUE IN TEACHING TRANSACTIONAL SPEAKING - Nur, Nur Aliyah (ETERNAL (English, Teaching, Learning, and Research Journal), 2018)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The research aimed to find out the effectiveness of describing and drawing picture technique in teaching transactional speaking at the second semester students of English Education Department at State Islamic University of Alauddin Makassar. This research employed quasi-experimental with non-equivalent control group design with pre-test and post-test. The population of this research was the second semester students of English education department at State Islamic University of Alauddin Makassar. The population was selected by using purposive sampling technique to determine the sample for experimental class and control class. The instrument used in this research was test. The test was used in the pre-test and post-test. The data indicated that there was a significant difference between the students’ post-test in the experimental class and post-test in the control class. Based on the findings of the research, the researchers concluded that describing and drawing picture technique was effective in teaching transactional speaking. Therefore, describing and drawing picture technique gave student opportunity to practice transactional speaking in classroom, it also could increase students’ motivation in learning in English since they feel their purpose of learning English so that they could use it and also could achieve it. The research aimed to find out the effectiveness of describing and drawing picture technique in teaching transactional speaking at the second semester students of English Education Department at State Islamic University of Alauddin Makassar. This research employed quasi-experimental with non-equivalent control group design with pre-test and post-test. The population of this research was the second semester students of English education department at State Islamic University of Alauddin Makassar. The population was selected by using purposive sampling technique to determine the sample for experimental class and control class. The instrument used in this research was test. The test was used in the pre-test and post-test. The data indicated that there was a significant difference between the students’ post-test in the experimental class and post-test in the control class. Based on the findings of the research, the researchers concluded that describing and drawing picture technique was effective in teaching transactional speaking. Therefore, describing and drawing picture technique gave student opportunity to practice transactional speaking in classroom, it also could increase students’ motivation in learning in English since they feel their purpose of learning English so that they could use it and also could achieve it. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="43" Name="Plain Table 3